Dietary linoleic acid requirements in the presence of α-linolenic acid are lower than the historical 2 % of energy intake value, study in rats. Issue 7 (19th March 2015) - Choque, Benjamin; Catheline, Daniel; Delplanque, Bernadette; Guesnet, Philippe; Legrand, Philippe
Abstract : Previous studies on rats and human subjects have established that the linoleic acid (LA) requirement is 2 % of the total energy intake (en%), but is obtained in the absence of α-linolenic acid (ALA) and consequently appear to be overestimated. This raises questions since a recent study including ALA has suggested to divide the historical value by four. However, this recent study has remained inconclusive because the animals used were not totally LA-deficient animals. For the first time, the present study was especially designed using physiological and biochemical markers and performed in two steps: (1) to achieve a specific n -6 fatty acid deficiency model using growing male rats fed either a 0 en% from LA/0 en% from ALA (0LA/0ALA), 0LA/0·5ALA or 2LA/0·5ALA diet, born from female rats fed a 0LA/0·5ALA diet; and (2) to refine the required level of LA in the presence of ALA using rats fed either a 0LA/0ALA, 0·5LA/0·5ALA, 1LA/0·5ALA, 1·5LA/0·5ALA diet, born from female rats fed a 0LA/0·5ALA diet. The first step shows that the best LA deficiency model was obtained using rats fed the 0LA/0ALA diet, born from female rats fed the 0LA/0·5ALA diet. The second step demonstrates that in growing rats, LA deficiency was corrected with an intake of 1–1·5 en% from LA and 0·5 en% from ALA. These data suggest that the requirements in humans should be revisited, considering the presence of ALA to set up the recommendation for LA.